PENGEMBANGAN APLIKASI PERPUSTAKAAN BERBASIS ANDROID Dl TRISAKTI SCHOOL OF MANAGEMENT - Yulianah Yulianah (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2017)
The high use of mobile devices like smartphones or tablets to access the internet is an opportunity as well as a challenge for libraries to expand digital service features. One form of potential digital services that can be implemented by TSM Library is an application library or mobile library applications based on Android. The development of Android-based library application as an effort to implement the function of TSM Library as information provider for all academic community will be one step forward, also promote the image of TSM Library as a library model that is able to innovate and catch up with the up-to-date information and communication technology.  The availability of Android-based TSM Library application on the Google Play Store that can be shared through several social medias like Facebook, Google+, Line, Path, Skype, Twitter, WhatsApp is an effective promotion to reach all the academic community without being constrained by space and time. The results of the study showed that the access to the database of TSM Library needs to be further developed by applying the concept of Android-based library applications with the main purpose of reaching users who are mostly from the internet generation.